Self-Image of Sufistic Da'i on Social Media: Analysis of Sufism Content for Students on Social Media - Muhammad Munir; Abdulloh Hanif; Md.Mosaddek Billah (Fakultas Usluhuddin dan Dakwah IAIN Kediri, 2024)
Social media, such as Facebook, Instagram, Twitter, and other platforms, have changed the way we communicate, interact, and share information. Additionally, social media also has a significant impact on the way we view ourselves and others. The problem with a consumptive society is that Sufism is less interesting. This is because social media users need entertainment that is not monotonous with one goal, requiring a diversity of ways to reach God's love. This research method uses content analysis with data collection and coding methods for important content on Habib Husain bin Ja'far Al Hadar S.Fil.I., M.Ag YouTube channel. His YouTube channel is called